Albendazole sulfoxide enantiomers: Preparative chiral separation and absolute stereochemistry - Lourenco, Tiago C.; Batista, Joao M. [UNESP]; Furlan, Maysa [UNESP]; He, Yanan; Nafie, Laurence A.; Santana, Cesar C.; Cass, Quezia B. (Elsevier B.V., 2012)
The enantiomeric separation of albendazole sulfoxide was carried out by simulated moving bed chromatography with variable zones (VARICOL). An overall recovery of 97% was achieved and enantiomeric ratios of 99.5% for raffinate and 99.0% for extract were attained. A total of 880 mg of (+)-albendazol sulfoxide and 930 mg of its antipode were collected after 55 cycles or 11 h of process, resulting in a mass rate of 2 g/day. Furthermore the absolute configuration of the enantiopure compounds was determined for the first time by vibrational circular dichroism (VCD) with the aid of theoretical calculations as (-)-(S) and (+)-(R)-albendazole sulfoxide. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Albendazole sulfoxide; Simulated moving bed chromatography; VARICOL process; Multimilligram enantiomeric separation; Vibrational circular dichroism; Absolute configuration